2018
DOI: 10.4996/fireecology.140112514
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Content, Ignitability, and Fire Risk of Vegetation in Vertical Greenery Systems

Abstract: Vertical greenery systems (VGS) are getting popular as a green cladding material. However, they have not been adequately assessed in terms of fire safety. Lack of maintenance and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Furthermore, both job roles were identified through literature review. However, various authors have identified the role of minimising construction waste (Boyle, 2014; Cruickshank and Fenner, 2007; Kelly, 2016; Qureshi and Nawab, 2013) as the job role rather than energy simulation (Dahanayake and Chow, 2018). Furthermore, the experts in the preliminary interview also validated that minimising construction waste is an important job role for engineers.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, both job roles were identified through literature review. However, various authors have identified the role of minimising construction waste (Boyle, 2014; Cruickshank and Fenner, 2007; Kelly, 2016; Qureshi and Nawab, 2013) as the job role rather than energy simulation (Dahanayake and Chow, 2018). Furthermore, the experts in the preliminary interview also validated that minimising construction waste is an important job role for engineers.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In addition, “knowledge on adapting renewable energy to the project in order to reduce the energy consumption of the project”, “efficient use of resources”, “knowledge of the location and geographical conditions of the project”, “improving methods to reuse and collect materials in construction and development” and “extracting natural resources” job roles were identified as high-importance job roles for engineers in relation to address the challenges associated with climate change. However, the “efficient use of resources” is the most cited job role in the literature review (Boyle, 2014; Cruickshank and Fenner, 2007; Dahanayake and Chow, 2018; Kelly, 2016). Finally, the results emphasised that “developing instrumentation for monitoring and measuring pollution” (RI – 0.568) is a job role of medium importance for Sri Lankan engineers to address the challenges associated with climate change.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are lightweight, weather-resistant and can be printed with almost any design, but are also flammable (Mazziotti et al , 2016). Furthermore, the green cladding system is composed of a wall of vegetation developing via a reinforced mesh or growing out of some substrate, which is commonly made of some combustible plastics (Dahanayake and Chow, 2018; Medl et al , 2017; Wong et al , 2010). To date, a limited published study has been carried out on the fire safety of these cladding systems.…”
Section: Fire Hazard Of Lightweight Cladding Systemsmentioning
confidence: 99%
“…Hence, the temperature increases, the relative humidity decreases, and the risk of ignition is heightened: “The moisture content is considered to be the most critical factor that affects the ignitability of vegetation […] It also impacts fire propagation […] Therefore, it becomes an essential indicator in fire risk analysis” (Dahanayake and Chow, pp. 127–128 in [ 24 ]). Therefore, measuring moisture in the litter layer could be useful as a predictive indicator for fire risk assessment if the measured value adequately accounts for the heterogeneity of the litter layer.…”
Section: Introductionmentioning
confidence: 99%